Study to Analyze the Effectiveness of Discovery Learning Model in Biology Learning - Andriani, Fitry Della; Abdullah, Renisa; Saputra, Hendra Eka; Jodion Siburian, Jodion; Sadikin, Ali; Mardiyanti, Lely (Bioilmi: Jurnal Pendidikan, 2024)
In teaching and learning activities on biology materials, educators are often faced with challenges to the ability of students to understand deep biological concepts. An innovation that is needed by educators is the determination of a learning model that adapts to students. The purpose of the research in this article is a rigorous and regular review of the effectiveness of the discovery learning model in learning biology. Literature review is a method used in this article research which is carried out by identifying, analyzing, describing, and making conclusions based on the relevance of the selected research results systematically. The results of the review of 10 articles show that learning biology using the discovery learning model can improve the ability to collaborate, and creative and critical thinking of students as well as the activeness and learning outcomes of students. Based on the results of the research, the use of the discovery learning model is very effective in the biology learning process in that it can improve students' learning outcomes, and critical thinking skills and increase students' motivation to learn.